PERAN INVESTASI INDUSTRI TERHADAP PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI DI INDONESIA - Handayani, Fitri (Islamic Economics and Business Faculty of UIN Antasari, 2014)
This paper aims to analyze the effect of industry investment towards employment of industry sector. Type of data in this paper is time series and secondary data. The study period is from 1990 until 2010. The estimation method is Error Correction Model (ECM) that able to show long-term and short-term relationship. The result shows that foreign investment has no significant effect to employment of industry sector in long-term in Indonesia. While in short term, the form of this investment has a significant effect and has a negative relationship to employment of industry sector with regression coefficient -207.68. In the other side, domestic investment has a significant and negative effect to employment of industry sector in Indonesia, both in long-term and short-term with each regression coefficient 61.53 and 235.42.